Exegetical Hybridity in Nusantara Qur’anic Interpretation: A Study of Marāḥ Labīd by Syekh Nawawi al-Bantani - Mutamakin; Nur Afiyah; Adel Ibrahim Al-Turki; Bakhruddin Fannani (QOF, 2025)
This article examines the exegetical hybridity in the book Tafsīr Marāḥ Labīd, a Qur’anic commentary authored by the nineteenth-century Javanese scholar Syekh Nawawi al-Bantani. By highlighting the marginalization of Southeast Asian voices in mainstream tafsīr studies, the research demonstrates how Nawawi creatively integrated classical Islamic scholarship from Ottoman-Ḥijāz networks with local Bantenese agrarian ethics. Through textual-historical criticism, comparative hermeneutics, and digital ethnography, the study reveals Nawawi’s systematic method: employing variant recitations (qirāʾāt) to produce context-sensitive legal rulings, filtering non-essential narratives (Isrāʾīliyyāt) to prioritize ethical lessons, and applying maqāṣid pragmatism to address both colonial and social injustices. This hybrid approach transformed Qur’anic exegesis into subtle resistance against Dutch land exploitation while simultaneously promoting communal welfare. Today, Marāḥ Labīd remains a living tradition within Indonesian pesantren, relevant to contemporary issues ranging from environmental stewardship and gender-inclusive ethics to social moderation and pandemic responses. The article underscores Nawawi’s legacy as a decolonial model, demonstrating that Nusantara scholarship has actively and sustainably shaped Islamic intellectual and social landscapes through adaptive fidelity to classical orthodoxy while enabling innovation in modern contexts.